2008
DOI: 10.1007/s10562-007-9391-3
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sulfur Tolerance of Bimetallic PtPd/Al2O3 Catalysts for Hydrogenation of Tetralin by Addition of Fluorine

Abstract: A series of mono-and bi-metallic Pt-Pd/Al 2 O 3 samples with and without F were studied as aromatic hydrogenation catalysts. The effects of changing the order of impregnation of the Pt precursor and F as well as varying the calcination temperature (300-500°C) were investigated. Temperature programmed reduction (TPR) results demonstrate the presence of a higher fraction of dispersed metal precursor species left on the surface from the impregnation (PtO x Cl y ) on the Pt/Al 2 O 3 sample calcined at high tempera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…In line with the literature data, the incorporation of Cl − ions onto the various supports, either as part of the Pt precursor (incomplete decomposition of H 2 PtCl 6 ) or after chlorination may bring the Brønsted sites to appear [56][57][58]. Jongpatiwut et al [59] have observed that halogenation (in his work fluorination) of Pt-Pd/Al 2 O 3 strongly increases the acidity of the catalysts. D'Ippolito et al [60] have also observed an acidity enhancement in the case of Pd catalysts as an effect of Cl − ions added, either by the Pd chlorinated precursors and/or by the added HCl during metal impregnation.…”
Section: Catalysts Characterisationsupporting
confidence: 66%
“…In line with the literature data, the incorporation of Cl − ions onto the various supports, either as part of the Pt precursor (incomplete decomposition of H 2 PtCl 6 ) or after chlorination may bring the Brønsted sites to appear [56][57][58]. Jongpatiwut et al [59] have observed that halogenation (in his work fluorination) of Pt-Pd/Al 2 O 3 strongly increases the acidity of the catalysts. D'Ippolito et al [60] have also observed an acidity enhancement in the case of Pd catalysts as an effect of Cl − ions added, either by the Pd chlorinated precursors and/or by the added HCl during metal impregnation.…”
Section: Catalysts Characterisationsupporting
confidence: 66%
“…In the region at 150 C, there is only H 2 consumption and the peak is attributed to Pt reduction. According to the literature, the lowest temperature peak can be assigned to the reduction of Pt oxide species weakly interacting with the support [46,47]. The signal at a higher temperature, 640 C, corresponds to the consumption of H 2 and the release of CO. For this reason, this peak is assigned to H 2 consumption by unsaturated sites and to the decomposition of the surface oxygenated groups of the C support.…”
Section: Catalyst Characterizationmentioning
confidence: 91%
“…The authors of [26][27][28][29] assumed that the first peak can be attributed to the reduction of oxy-or hydroxychloride platinum species, while the high temperature peak can be attributed to the two-dimensional dispersive oxychlorinated platinum species, which strongly interact with the alumina support. It should be noted that the above conclusions are generally accepted.…”
Section: Tpr Xrd and Tof-sims Analysismentioning
confidence: 99%